The phenomenon of unauthorized release of physical education in the Czech education system - Ondřej Ješina (Palacký University Olomouc, 2017)
Background: Despite the existence of international agreements and strategic documents, but also the experience from abroad is gratuitous release of school physical education in our reality, and often used practice. On the one hand, pupils with disabilities (or other special educational needs), who attend the school primarily intended for them, participating in all the compulsory subjects, including physical education, on the other hand, then on the mainstream schools pupils with far fewer health problems don't realize physical education with reference to health complications, which could potentially cause such participation. Objective: The aim of the paper is to highlight some of the negative effects in the application of norms and standards in relation to the release of the pupils of the school of physical education at the elementary and secondary schools. Methods: The main method is the analysis of relevant sources, in particular the legislative standards. Results: The present contribution allows you to discuss over some passages of Act no. 561/2004 Coll. relating to the issue. It draws attention to the decree of Ministry of health no. 391/2013 which aims to act preemptively to protect the health of children and adults in the branch of sport, leisure activities and school physical education. For this reason, this Decree establishes a system for medical examinations and restricts or prevents access to mobility activities for selected groups of persons. Conclusions: We evaluate negatively in particular the fact that the legislative standards declare the possibility of release from the school of physical education menu without menu alternatives, which we consider to be the wrong decision of our legislators. The application of the relevant laws and decrees still creates barriers to access of some children, pupils and students for mobility activities, in particular pupils with special educational needs.